Analysis of Joint Constraint Reaction of Spatial 3-UPS Parallel Mechanism - Baozhou Shi; Wei Wei; Xiujie Xu; Zhenkai Li (Jixie chuandong)
In light of the complexity of calculation of joint force of spatial mechanism system，a mechanical analysis of joint constraint reaction of 3-UPS Parallel mechanism is carried out. Considering the relationship between Lagrange multiplier and constraint reaction of spatial mechanism，the joint reaction of the spatial parallel mechanism is calculated based on Lagrange augmented method. At the same time，the calculation results are verified by Newton Euler method and Adams and Matlab Software co-simulation，and a comparative analysis of the two results is conducted. The results show that the size of the joint constraint reaction of the spatial mechanism calculated by the two methods is basically the same，and the error is between 0.5% and 1.2%，which is relatively small. The correctness of the method of using Lagrange multiplier and Lagrange augmented method to calculate the joint constraint reaction of spatial mechanism is verified，and a certain reference for the mechanical analysis of spatial mechanism is provided.